EVALUATION OF YIELD AND QUALITY ASPECTS OF INDIAN MUSTARD (BRASSICA JUNCEA L. CZERNJ & COSSON) UNDER INTEGRATED NUTRIENT MANAGEMENT - Singh, RAJU; Singh, S.K (Annals of Agricultural Research, 2014)
Field experiment was carried out during rabi seasons of 2001-02 and 2002-03 to evaluate the response of Indian mustard cv. RH-30 to farmyard manure (2.5 and 5 t/ha), inorganic N (0,40,80 kg/ha) in combination biofertilizers (Azotobactor chroococcum and Azospirillum). Branches, siliquae/plant, seeds/ siliquae, 1000-seed weight seed oil content and oil yield of Indian mustard and yield of seed and stover. Increased significantly with the application of farmyard manures (5 t/ha + Azotobactor chroococcum + Azospirillum) over the control. Application of N showed liner increase of the characters up to 80 kg/ha.